nArgBP2 together with GKAP and SHANK3 forms a dynamic layered structure - Lee, Sang-Eun; Chang, Sunghoe (Frontiers in Cellular Neuroscience, 2024)
nArgBP2, a protein whose disruption is implicated in intellectual disability, concentrates in excitatory spine-synapses. By forming a triad with GKAP and SHANK, it regulates spine structural rearrangement. We here find that GKAP and SHANK3 concentrate close to the synaptic contact, whereas nArgBP2 concentrates more centrally in the spine. The three proteins collaboratively form biomolecular condensates in living fibroblasts, exhibiting distinctive layered localizations. nArgBP2 concentrates in the inner phase, SHANK3 in the outer phase, and GKAP partially in both. Upon coexpression of GKAP and nArgBP2, they evenly distribute within condensates, with a notable peripheral localization of SHANK3 persisting when co-expressed with either GKAP or nArgBP2. Coexpression of SHANK3 and GKAP with CaMKIIα results in phase-in-phase condensates, with CaMKIIα at the central locus and SHANK3 and GKAP exhibiting peripheral localization. Additional co-expression of nArgBP2 maintains the layered organizational structure within condensates. Subsequent CaMKIIα activation disperses a majority of the condensates, with an even distribution of all proteins within the extant deformed condensates. Our findings suggest that protein segregation via phase separation may contribute to establishing layered organization in dendritic spines.